2020
DOI: 10.21608/ijma.2020.21730.1068
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Ombitasvir/Paritaprevir/Ritonavir plus Ribavirin in Treatment of Chronic Hepatitis C Patients with End Stage Renal Disease on Regular Hemodialysis

Abstract: Background: Hepatitis C virus [HCV] infection is associated with more significant morbidity and mortality among dialysis patients than in healthy populations. The fixed-dose tablet [ombitasvir/ paritaprevir/ritonavir] in combination with ribavirin was effective and generally well tolerated in treatment of chronic HCV infected patients with end stage renal disease [ESRD] on hemodialysis. However, limited published data are known about the usefulness of this regimen for treatment of HCV patients with ESRD on he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
(8 reference statements)
0
1
0
Order By: Relevance
“…The Egyptian protocol recommends ombitasvir/paritaprevir/ritonavir with ribavirin in management of HCV patients with renal impairment. [ 24 ] As this study was a real life experience in daily HCV management practice in Egypt, it reported that Paritaprevir/ritonavir and ombitasvir plus ribavirin for 12 weeks was considered to be safe and effective in the treatment of chronic HCV infected patients with varying degrees of renal impairment.…”
Section: Discussionmentioning
confidence: 99%
“…The Egyptian protocol recommends ombitasvir/paritaprevir/ritonavir with ribavirin in management of HCV patients with renal impairment. [ 24 ] As this study was a real life experience in daily HCV management practice in Egypt, it reported that Paritaprevir/ritonavir and ombitasvir plus ribavirin for 12 weeks was considered to be safe and effective in the treatment of chronic HCV infected patients with varying degrees of renal impairment.…”
Section: Discussionmentioning
confidence: 99%